2002
DOI: 10.1212/wnl.59.8.1246
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced temporal lobe epilepsy

Abstract: Although precipitation of seizures by exercise has been described, the reproducible induction of temporal lobe seizures by exercise is unusual. The authors report two patients with left temporal lobe seizures induced by exercise. In one patient the family history suggested autosomal-dominant inheritance. Prolonged hyperventilation, simple movements, and visualization of a competitive game did not produce epileptiform discharges on the interictal EEG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 11 publications
3
31
0
3
Order By: Relevance
“…This finding of fear as an exercise deterrent is in accordance with current research [1,4,7,8,10,30,31], however, the qualitative approach taken allowed for the diverse ways in which fear manifested itself to be revealed. Such manifestation included the fear that seizures could prevent Maya from achieving her end goal and would cause teammates to keep away from Andrew at the gym, as well as create the feelings of a loss of independence for Rose and Gwen.…”
Section: Discussionsupporting
confidence: 88%
“…This finding of fear as an exercise deterrent is in accordance with current research [1,4,7,8,10,30,31], however, the qualitative approach taken allowed for the diverse ways in which fear manifested itself to be revealed. Such manifestation included the fear that seizures could prevent Maya from achieving her end goal and would cause teammates to keep away from Andrew at the gym, as well as create the feelings of a loss of independence for Rose and Gwen.…”
Section: Discussionsupporting
confidence: 88%
“…Simulation of this exercise involving limb movements, riding a stationary exercise bicycle, hyperventilation and imagined cycling did not provoke seizures. Accordingly, these authors suggested that reflex precipitation of temporal lobe seizures requires integration of complex stimuli within limbic structures [7]. Similarly, our patient had olfactory hallucinations only in certain real situations where unpleasant smells were possible, although actual foul odors were absent.…”
Section: Discussionsupporting
confidence: 55%
“…In some cases of reflex epilepsy, precipitating factors are complex and combine multiple sensory modalities [5]. For example, cases of exercise-induced temporal lobe epilepsy reported by Sturm et al [7] included a patient who experienced seizures only while actually riding a bicycle. Simulation of this exercise involving limb movements, riding a stationary exercise bicycle, hyperventilation and imagined cycling did not provoke seizures.…”
Section: Discussionmentioning
confidence: 99%
“…De manera excepcional se ha documentado que pocas personas con la enfermedad desarrollan crisis provocadas por la actividad física (84)(85)(86)(87)(88)(89)(90). Arida y colaboradores (91) relacionan la aparición de estos eventos con alteraciones homeostáticas asociadas a fatiga, estrés, hipoxia, hipoglicemia, hiperhidratación, hiponatremia o hipertermia.…”
Section: ¿Puede La Actividad Física Inducir Crisis Epilépticas?unclassified